Analytical study of MHD stagnation point flow with the impact of thermal radiation and viscous dissipation over stretching surface - Rehman, Ali; Ahmad, Sohail; Alqahtani, Salman A.; İnç, Mustafa; Rezapour, Shahram; Alqahtani, Nouf F.; Pathak, Pranavkumar (World Scientific Publ Co Pte Ltd, 2025)
This study examines the analytical study of magnetic hydrodynamic stagnation point flow with the impact variable viscosity on a movable surface along with the impact of thermal radiation. The problem is modeled with the help of momentum and energy conservation laws in the form of NLPDEs. The novelty of this study is the combined impact of variable viscosity and thermal radiation with the analytical method. Aluminum oxide nanoparticles and water are used as base fluids in this research work. The authors applied appropriate transformations to convert a collection of dimension forms of NLPDEs to dimensionless forms of NODEs. The transformed NODEs are solved with the help of an approximate analytical method known as the HAM. The effects of different parameters, including electric field, magnetic field, stagnation point flow, thermal radiation PN, and EN on energy and momentum profiles intended, and the results are planned with the help of graphs.
Keywords: Thermal radiation; HAM; stretching surface; momentum and energy conservation laws